Status of childhood vaccination practice in a fixed-session site of a Medical College of Eastern India - Raj, Shivangi; Kesharwani, Shweta; Kumari, Shweta; Kumari, Soni; Mitra, Satabdi; Dasgupta, Samir (The ESRF Research Journal for Undergraduate Medical Students, 2024)
Introduction: Vaccination is most cost-effective munitions and National Immunization Schedule (NIS) is providing protection to under-five children against 11 diseases currently. Still gap of nearly 1/3rd unvaccinated children is remaining despite various initiatives, campaigns, and special drives. Objective: To assess status of vaccination service and awareness among various stakeholders of an immunization clinic in a medical college hospital in a metropolitan city of eastern India. Materials and Methods: An observational qualitative study with cross-sectional design was conducted over 4 months in an immunization clinic of a medical college. With Ministry of Health and Family Welfare (MoHFW) prescribed checklist, session site was observed with non-participant stance, two vaccinators being public health nurses were interviewed and 35 caregivers of beneficiaries were interviewed at exit point. Results: Regarding session and logistics, adherence to NIS guidelines was observed mostly with few gaps in injection safety and hand washing practices. Except for one non-updated NIS schedule and one bio-medical waste management, no other IEC material could be noted at site. Only 28.6% of caregivers were found as aware of vaccines given to their children that day though importance of keeping mother-child protection card and noting of next vaccine date was among majority. AEFI knowledge was among 40% of caregivers and only 11.4% could say that “seven” visits up to 5 years of age are required for their children to get “completely immunized”. Conclusion: Despite commendable commitment and support from service side childhood vaccination is at stake which requires more advocacy, in-service training and supportive supervision.